2010
DOI: 10.1103/physrevb.81.033304
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity dependence of photocurrent gain in single-crystal diamond detectors

Abstract: The authors report on the photocurrent gain in a diamond photodetector that has two nonohmic contacts connected back-to-back. This photocurrent gain strongly depends on both the deep-ultraviolet ͑DUV͒ light intensity and the applied voltage. In addition, the gain is accompanied by a slow response. The gain is observed to originate from a metal/diamond interface trap center. Numerical analysis discloses that the photocurrentvoltage characteristics follow thermionic-field emission tunneling at low DUV light inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 13 publications
0
53
0
1
Order By: Relevance
“…8,18 Moreover, doping can introduce dangling bonds, trap states and deep levels on the nanostructures, which can decrease the electron-hole recombination and prolong the photocarrier lifetime, resulting in enhanced EQE. 27 In tin-doped CdS nanowires, the below bandgap energy light response should originate from the excitation into the mid-gap electronic state. Zhang M. Y. et al have demonstrated that the incorporation of Sn can introduce both donor and acceptor levels due to the amphoteric nature of tin.…”
Section: Resultsmentioning
confidence: 99%
“…8,18 Moreover, doping can introduce dangling bonds, trap states and deep levels on the nanostructures, which can decrease the electron-hole recombination and prolong the photocarrier lifetime, resulting in enhanced EQE. 27 In tin-doped CdS nanowires, the below bandgap energy light response should originate from the excitation into the mid-gap electronic state. Zhang M. Y. et al have demonstrated that the incorporation of Sn can introduce both donor and acceptor levels due to the amphoteric nature of tin.…”
Section: Resultsmentioning
confidence: 99%
“…[38,40] Moreover, the role of oxygen in the photoresponse process can be revealed by the comparison of response behavior in air and in vacuum. As shown in Figure 7d larger than that in air but the response rate in vacuum is relative slower ( Figure S6, Supporting Information).…”
Section: Optical/optoelectronic Properties Of Res 2 Flake and Continumentioning
confidence: 99%
“…[ 18 ] In addition, the simultaneous achievement of both high R λ (or QE) and fast response time reveals that trapping due to bulk defects and the recombination due to surface absorption are possibly in an excellent balance for practical needs. [ 26 ] In summary, single-crystalline ZrS 2 nanobelts have been assembled into FETs and photodetectors. Electrical transport properties were investigated, from which the basic electrical parameters, such as mobility and electron concentration, were revealed.…”
Section: Supporting Informationmentioning
confidence: 99%